Fuel Cell Electronics Packaging - Kuang, Ken.; Easler, Keith; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Today's commercial, medical and military electronics are becoming smaller and smaller. At the same time, these devices are packed with more functions and demand more power. This power requirement is currently met almost exclusively by battery power. A fuel cell is like a battery converting chemical energy directly to electricity. The convergence of fuel cell technology and microelectronics is enabling the new design and manufacturing of fuel cells. Fuel Cell Electronics Packaging presents the latest developments in the technology convergence of microelectronics and fuel cells. Using the well established manufacturing methods used in microelectronics packaging, fuel cells can be further fabricated in smaller sizes with higher energy density, at a faster pace and lower cost. This book uniquely addresses this issue. Fuel Cell Electronics Packaging serves as a practical reference guide for engineers, researchers, and manufacturers of microelectronic and fuel cell products who are interested in topics such as: ceramic hybrid separators for micro fuel cells miniature fuel cells built with LTCC technology novel fuel cells fabricated using microelectronics technology fuel cell thermal management Written by a variety of professional and academic sources, Fuel Cell Electronics Packaging is a valuable resource for those interested in the latest advances in fuel cell technology.
to Fuel Cell Technology -- Stable Glass Seals for Intermediate Temperature (IT) SOFC Applications -- A Novel Technology of Solid Oxide Fuel Cell Fabrication -- In Situ Seal Integrity Sensing for Solid Oxide Fuel Cells -- Solid Oxide Fuel Cell -- Benefits and Test Results of a Ceramic Separator Component for Micro Fuel Cells -- Foil Type Micro PEM Fuel Cell with Self-Breathing Cathode Side -- Thermal Constraints of PEM Micro Fuel Cells for Portable Electronics -- A Direct Methanol Fuel Cell Using Cermet Electrodes in Low Temperature Cofire Ceramics -- Automated Fluid Dispensing for Fuel Cell Manufacture and Assembly -- Ink-Jet as Direct-Write Technology for Fuel Cell Packaging and Manufacturing.
Keywords: Chemistry; Renewable energy resources; Electrochemistry; Renewable energy sources; Alternate energy sources; Green energy industries; Chemistry; Electrochemistry; Renewable and Green Energy; Renewable and Green Energy; Electronic books